2016
DOI: 10.1016/j.virol.2016.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and modeling of a strain-specific epitope in the Norwalk virus capsid inner shell

Abstract: Noroviruses are diverse positive-strand RNA viruses associated with acute gastroenteritis. Cross-reactive epitopes have been mapped primarily to conserved sequences in the capsid VP1 Shell (S) domain, and strain-specific epitopes to the highly variable Protruding (P) domain. In this work, we investigated a strain-specific linear epitope defined by MAb NV10 that was raised against prototype (Genogroup I.1) strain Norwalk virus (NV). Using peptide scanning and mutagenesis, the epitope was mapped to amino acids 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…A total of 23 recombinant scFvs have been produced for HuNoV (Tables S1–S3). Due to their smaller size, HuNoV epitope mapping with scFvs and VHHs has led to the characterization of several conserved regions buried within VLPs, which conventional mAbs have typically failed to recognize [129,130,132]. These mAbs have elucidated novel ways in which humoral immunity might be harnessed to neutralize infection and have therapeutic potential due to their versatility in genetic engineering and delivery to the site of infection.…”
Section: Isolation and Characterization Of Norovirus Monoclonal Anmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 23 recombinant scFvs have been produced for HuNoV (Tables S1–S3). Due to their smaller size, HuNoV epitope mapping with scFvs and VHHs has led to the characterization of several conserved regions buried within VLPs, which conventional mAbs have typically failed to recognize [129,130,132]. These mAbs have elucidated novel ways in which humoral immunity might be harnessed to neutralize infection and have therapeutic potential due to their versatility in genetic engineering and delivery to the site of infection.…”
Section: Isolation and Characterization Of Norovirus Monoclonal Anmentioning
confidence: 99%
“…Though less conserved than S domain sequences, residues that make up the P1 domain are more readily accessible due to capsid flexibility [98]. Cross-reactive mAbs that map to linear epitopes have proven useful in diagnostic assays, but their protective capacity appears limited [132,133,134].…”
Section: Isolation and Characterization Of Norovirus Monoclonal Anmentioning
confidence: 99%
“…To identify how BtCalV/A10 and BtNoV are related to known Caliciviridae capsid sequences, we analyzed the amino acid sequences of the conserved shell (S) domain of the capsid protein due to the extensive variability within the protruding domain of the VP1 capsid protein ( 57 , 58 ). We generated S domain phylogenetic trees and cladograms from 51 known calicivirus S domain sequences ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the S domain is a conserved region within VP1 and have described the icosahedral scaffold of VP1, and a recent study reported that the S domain of a NoV strain contains strain-specific epitopes that contribute to antigenic diversity [28]. This region in strain CH-HNSC-2018 included a 134A unique aa mutation compared with the other NoV strains.…”
Section: Discussionmentioning
confidence: 99%